El “sombrero frigio”. Valores, símbolos e iconografía en la tradición republicana cubana independentista - Guanche, Julio César (El Colegio de México, A.C., 2024)
This article studies one aspect of the Cuban republican tradition, exploring how republican ideas were appropriated and recreated in the context of the War of Independence and through which symbols Cuban actors elaborated their own ideas regarding this political current. It concentrates on an analysis of iconography, a body of sources that has been little studied in the Cuban historiography. It identifies ambiguities and tensions that influenced the independence process, suggesting how ideas regarding independence and the republic were produced “from below” in Cuba. This article thus contributes to restoring the place of republicanism as a central tradition of Cuban political history, not as an echo of projects from abroad, but as the result of grassroots political production.